Lactoferrin as a Marker of Chronic Telogen Effluvium in Premenopausal Women - Alaa F Hasseeb (Journal of Global Pharma Technology, 2016)
Aim: Evaluation of serum Lactoferrin, Hb and ferritin levels in females with chronic telogen effluvium (CTE) or acute telogen effluvium (ATE), in order to validate their role in these common hair loss diseases. Methods: Fifty three females (aged range 18 - 45 years) with hair loss, in the form of TE (ATE=27 as G2, group aged range18-35), (CTE=26 as G3 group aged range 18-45), and 26 age-matched females with no hair loss (as G1 group), were included in the study. Diagnosis was based upon clinical examination as well as dermoscopy. Serum Lactoferrin and ferritin levels were determined for each participant. Results: Serum lactoferrin levels showed highly significant differences (p= 0.00) in the comparison of chronic TE (G3) and Acute TE (G2) (7.68±2.13 ng/ml vs. 4.65±2.18 ng/ml), Also between (G1) and (G3) (5.21±1.03 ng/ml vs. 7.68±2.13 ng/ml), but there is no significant difference between (G1) and (G2) (5.21±1.03 ng/ml vs.4.65±2.18 ng/ml).Plasma ferritin level showed highly significant decrease (p=0.001) in comparison (G1) group and (G2) group(50.72±11.17 µg/dl vs. 36.49 ±15.04µg/dl ) respectively ,Also showed highly significant decrease (p=0.00) between (G1) group and (G3)( 50.72±11.17 µg/dl vs.31.98± 15.98 µg/dl) but there is no significant difference(P=0.47) between (G2) and (G3) (36.49 ±15.04 µg/dl vs. 31.98± 15.98 µg/dl).Hemoglobin level showed highly significant decrease (p=0.028) in (G1) and (G2) (12.89±0.70 mg/dl vs. 12.15±1.19 mg/dl) respectively, Also showed highly significant decrease (p=0.00) between (G1) and (G3) (12.89±0.70 mg/dl vs. 11.60±1.09 mg/dl ), but there is no significant difference(P=0.12) between (G2) and (G3) (12.15±1.19 mg/dl vs. 11.60±1.09 mg/dl). Conclusion: High serum Lactoferrin is associated with hair loss in females with CTE, while low levels of ferritin are associated in ATE and CTE. Screening to establish ferritin levels in cases of hair loss and supplementing with them when they are deficient may be beneficial in the treatment of disease.Keywords: Lactoferrin, Telogen effluvium, Ferritin, Transferrin